Membrane adhesion via homophilic aaccharide-aaccharide interactions investigated by neutron scattering - Schneck, Emanuel; Demé, Bruno; Gege, Christian; Tanaka, Motomu (Biophysical journal, 2011)
Solid-supported membrane multilayers doped with membrane-anchored oligosaccharides bearing the LewisX motif (LeX lipid) were utilized as a model system of membrane adhesion mediated via homophilic carbohydrate-carbohydrate interactions. Specular and off-specular neutron scattering in bulk aqueous electrolytes allowed us to study multilayer structure and membrane mechanics at full hydration at various Ca2+ concentrations, indicating that membrane-anchored LeX cross-links the adjacent membranes. To estimate forces and energies required for cross-linking, we theoretically modeled the interactions between phospholipid membranes and compared this model with our experimental results on membranes doped with LeX lipids. We demonstrated that the bending rigidity, extracted from the off-specular scattering signals, is not significantly influenced by the molar fraction of LeX lipids, while the vertical compression modulus (and thus the intermembrane confinement) increases with the molar fraction of LeX lipids.